All aboard the dinotrain - Lund, Deb.; Fine, Howard, 1961- (Orlando : Harcourt, 2006)
When dinosaurs seek adventure by taking a train ride, they find the trip has some unexpected surprises along the way.
Accelerated Reader AR
Reading Counts RC
Keywords: Dinosaurs -- Juvenile fiction; Railroad trains -- Juvenile fiction; Travel -- Juvenile fiction; Stories in rhyme -- Juvenile fiction; Railroad stories; Dinosaurs -- Fiction; Railroad trains -- Fiction; Travel -- Fiction; Stories in rhyme; Dinosaures -- Romans, nouvelles, etc. pour la jeunesse; Voyage -- Romans, nouvelles, etc. pour la jeunesse; Romans, nouvelles, etc. pour la jeunesse; Dinosaurs; Railroad trains; Stories in rhyme; Travel; Dinosaurs -- Fiction; Railroads -- Fiction; Stories in rhyme; Travel -- Fiction; Picture books for children; Picture books; Stories in rhyme -- Juvenile; Picture books; Stories in rhyme; Fiction; Juvenile works; Stories in rhyme